Numerical analysis of photonic crystal fibres - Zdanowicz, Mariusz Rafal (2008)
Numerical methods for the simulation of photonic structures bring serious advantages in the field of research and design. Well prepared modelling techniques allow simulation of the demanded characteristics prior to fabrication of the device, or in some case the experimentally observed properties of fabricated devices to be understood in detail.